Transport Properties of a GaAs/InGaAs/GaAs Quantum Well: Temperature, Magnetic Field and Many-body Effects - Truong, Van Tuan; Nguyen, Quoc Khanh; Vo, Van Tai; Dang, Khan Linh (Communications in Physics, 2020)
We investigate the zero and finite temperature transport properties of a quasi-two-dimensional electron gas in a GaAs/InGaAs/GaAs quantum well under a magnetic field, taking into account many-body effects via a local-field correction. We consider the surface roughness, roughness-induced piezoelectric, remote charged impurity and homogenous background charged impurity scattering. The effects of the quantum well width, carrier density, temperature and local-field correction on resistance ratio are investigated. We also consider the dependence of the total mobility on the multiple scattering effect.